How Advanced Is Our Understanding of the Role of Intestinal Barrier Dysfunction in the Pathogenesis of Recurrent Urinary Tract Infections - Stepanova, Natalia (Frontiers in Pharmacology, 2022)
A comprehensive understanding of urinary tract infections (UTIs), one of the most common human infections, is required as they are complex and a poorly understood disease. Periurethral and vaginal colonization by rectal flora, with the constant presence of pathogens in the urethra, is the initial step of the recurrent UTIs pathway. Current scientific data describes the genetic, etiological, biological, and behavioral risk factors for recurring UTIs, but it does not include the effect of intestinal barrier function on the disease. Although gut microbiota has been proposed to be the main source for UTIs, the cross-talk between intestinal barrier dysfunction and the recurrence of UTIs has not yet been supported by scientific data. In this opinion review, based on published data and the results of our clinical studies, we aimed to outline the possible contribution of intestinal barrier dysfunction to the pathogenesis of RUTIs. We believe that the unanswered questions raised by this review can guide further experimental and controlled studies to clarify the mechanisms underlying the role of intestinal barrier dysfunction in the pathogenesis of RUTIs.